Organized management of decentralized economic production systems with joint implementation of development projects - Korneyev, Maxim; Pylypenko, Аndriy; Popov, Oleksandr; Shmatko, Nataliia (Eastern-European Journal of Enterprise Technologies, 2019)
Since integration and cooperation of enterprises have become important preconditions for the success of their operation, the organization of management of integrated economic production systems must thus take into account the features of decentralized decision-making by locally optimized economic entities. In this regard, the aim of the work was to establish a theoretical basis for the organization of management of joint implementation of development projects by participants of decentralized economic production systems based on business engineering technology. The hypothesis of the study is that such organizational regulation of interaction can be implemented through the creation of a set of business rules distributed among the participants of an economic production system. The regulation of business rules and the organization of communications between economic agents are implemented using the Design and Engineering Methodology for Organizations, DEMO. Within the framework of applying the DEMO methodology, a set of key roles of the stakeholders is defined. The set of top-level communication models of the participants of economic production systems has been developed, and groups of rules for maintaining the sustainability of the economic production system have been identified. The resulting models can be correlated with the standards of architectural modelling of complex systems. The logic of this correlation is represented by the example of the ArchiMate architectural modelling language. The relevance of this correlation is due to the creation of a basis for the deployment of a corporate information system and optimization of business processes of the economic production system.